Enhanced Anticancer Effect of Vincristine with Methionine Infusion after Methionine‐depleting Total Parenteral Nutrition in Tumor‐bearing Rats - Goseki, Narihide (Jpn J Cancer Res, 1996)
Methionine‐depleting total parenteral nutrition (Met(−) TPN), in which an amino acid solution devoid of L‐methionine and L‐cysteine is infused, is thought to reduce tumor cell growth through acting as a partial late S‐G(2) (i.e., late‐S and G(2) phases) blocker. The antitumor effect of vincristine (VCR), which acts on mitotic phase cells, was examined with methionine infusion immediately after Met(−) TPN in Yoshida sarcoma (YS)‐bearing rats. Rats were given Met(−) TPN for 8 days immediately after inoculation with YS cells (days 0 to 8), which was followed by methionine‐containing (Met(+)) regular TPN for 3 days (days 9 to 11) along with intraperitoneal administration of 0.05 mg/kg/day VCR. All rats were then fed solid food and water ad libitum until they died, with 0.1 mg/kg VCR administration on days 12 and 13. As controls, a Met(−) TPN only group, Met(+) TPN groups with and without VCR, and freely fed groups with and without VCR were studied. The progression of YS was markedly suppressed by Met(−) TPN with VCR. The median survival time in days was 25 days, significantly longer (P<0.001) (generalized Wilcoxon's tests) by 11 to 14 days than that of any of the other groups. In conclusion, VCR appears to have greater efficacy as an anticancer agent when administered together with methionine after Met(−) TPN.